Proses Komunikasi Informasi Edukasi pada Program Keluarga Berencana - Retno Heru Setyorini; Era Revika; Riadini Wahyu Utami (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2020)
Background: The contraceptive method that is most in demand by the public is the injection typecontraceptive method, even though the IUD and Implant are more effective. Cadres, Family PlanningField Officers, and Midwives are officers who directly carry out IEC on contraceptives for fertile agedcouples. The poor quality of IEC will affect the receipt of information about IUD contraceptives andimplants.Objective: The purpose of this study was to determine the implementation of IEC in the FamilyPlanning Program in improving IUD and implantsMethods: This study is a qualitative study with a case study design. The unit of analysis in this study is at the individual level. Research subjects for the qualitative study were 1 person from P3AP2KB Sleman Regency, namely the Head of IEC, 4 Family Planning Field Officers, 17 family planningcadres, and 4 PUS, 2 midwives in the Moyudan Health Center and Mlati Health Center. The samplingtechnique was done by using purposive sampling technique. Data analysis was performed by usingexplanation techniques (explanation building)Results: Cadres and Family Planning Field Officers do not use the media optimally and materialpresented is limited. The obstacles experienced by cadres in the Information and EducationCommunication process were not mastering the material and not having the skills to do IEC, while theobstacles experienced by Family Planning Field Officers were a lack of Human Resources and adouble workload so they could not directly provide IEC to couples of childbearing age.Conclusion: The implementation of Information and Education Communication for Fertile Couples byCadres and Family Planning Field Officers generally does not work properly. The impact is that manyfertile aged couples do not use contraceptives.Keyword: Communication, Information, Education, Family Planning